Comunidade de pescadores artesanais no Lago de Itaipu - conflitos territoriais na Colônia Z11 de São Miguel do Iguaçu/PR - Ferreira, Graziele (2014)
This research aims to analyze the formation of the fishing territory in Itaipu Lake, specifically in the fishing town of Colony Z11, in São Miguel do Iguaçu, Paraná State, Brazil. The element that motivated the study was the understanding of the formation process of this fishing territory: a territory built (from flooding), imposed on the population, with varied uses and conflicts involving different actors with different interests, such as artisanal fishermen and small farmers, Ministry of Fisheries and Aquaculture, Fishing Colony and ItaipuBinacional. For this study, the methodology used was based on literature reading, on statistics survey of artisanal fisheries in Brazil and in the Itaipu Lake, as well as on public policy in the fishing sector, on the historical process of fishing colonies, and on field work that include interviews and questionnaires. From our results, it is worth noting that the fisherman of Colony Z 11 is a fisherman because of the reality imposed; he fishes in an artificial lake, a territory full of varied subjects and conflicts; practices pluriactivities; lives in a discontinuous community (geographically distant from each other); and fishing, besides craft, is an important source of income. Nevertheless, reality shows the activity weakened by the difficulties in the extraction, production and marketing of fish circuit. In the riverine communities of Itaipu Lake, many family farmers, farm workers and even urban farmers began to engage in fishing activities frequently since the formation of Itaipu Lake. This new alternative income and life spans customs, way of life, now interrelated, forming a new territory as a result of upgrading and new power relations. This new social subject reinvents itself and expands territorially, in a conflictual space.